Calculus

Verify the identity. (Left side to right side)

{(sinu+sinv)/(cosu+cosv)}=tan1/2(u+v)

asked by DAS

Respond to this Question

First Name

Your Response

Similar Questions

  1. Pre-calculus

    Verify the identity (Left side to right side). {(cosu-cosv)/(cosu+cosv)}=-tan1/2(u+v)tan1/2(u-v)
  2. calculus

    Verify the identity: arctanx + arctan(1/x)=∏/2 using calculus theory. (Hint: Differentiate the left hand side of the identity)
  3. Algebra2 Verify Identity

    Verify the Identity: csc(x)+sec(x)/sin(x)+cos(x)=cot(x)+tan(x) the left side of the equation is all one term.
  4. solving trig. equations

    tan(3x) + 1 = sec(3x) Thanks, pretend 3x equals x so tanx + 1 = secx we know the law that 1 + tanx = secx so tanx + 1 becomes secx and... secx = secx sec(3x) = sec(3x) [just put 3x back in for x- you don't really have to change 3x
  5. trig...again

    gahh i cant figure this one out either. you have you verify the identity only using one side of the equation: sec^2x*sin^2x+sec^2x=-1 this identity cannot possible be true. on the left side you are adding 2 squared quantities, how
  6. Trigonometric Identities

    Verify/prove the following: (sinA+tanA)/(1+secA) = sinA ______________________________ tanu = 1+sinu-cos^2u/cosu(1+sinu) __________________________________ cotu = (2+cscu/secu)-2cosu ______________________________
  7. trig

    find the exact value of sinu/2, given that cosu=-4/5 and pi/2less than u less than pi
  8. trig

    Okay, I've been getting some of these, but I can't seem to verify this identity... any help? Here's the problem Sin(x+y) + Sin(x-y) = 2sinxcosy Okay, I've been working on the left side, and distribute, getting: Sinx + Siny + Sinx
  9. trig

    it says to verify the following identity, working only on one side: cotx+tanx=cscx*secx Work the left side. cot x + tan x = cos x/sin x + sin x/cos x = (cos^2 x +sin^2x)/(sin x cos x) = 1/(sin x cos x) = 1/sin x * 1/cos x You're
  10. Math: Intro to Vectors

    Left side = right side check type of question. x - (x + y)/2 = (x - y)/2 What I did was times the x in the left side by 2. I got: =(2x-x+y)/2 which equals =(x+y)/2 But the left side is (x-y)/2. What am I doing wrong?

More Similar Questions